STUDENT'S RESPONSE TO SMART APPS CREATOR MEDIA BASED ON THE LOCAL WISDOM OF MANTINGAN MOSQUE JEPARA TO INCREASE THE UNDERSTANDING ON THE CONCEPT OF GEOMETRY IN ELEMENTARY SCHOOL - Latif, Abdul; Utaminingsih, Sri; Su’ad, Su’ad (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
The purpose of this research was to analyze students’ response to Smart Apps Creator (SAC) media based on the local wisdom of Mantingan Mosque Jepara to improve the understanding of the concept of geometry at grade VI of the elementary schools in Kecamatan Kembang, Kabupaten Jepara. This research was Research and Development (R&D) using the method by Sugiyono at level 4. This research was conducted in seven steps, namely: 1) potential and problems, 2) literature study and information collection, 3) product design, 4) design validation, 5) design revision, 6) product manufacture, and  7) limited trial. The subjects of this study were 52 grade VI students at SD N 4 Cepogo, SDN 1 Bucu, and SDN 2 Bucu, Kecamatan Kembang, Kabupaten Jepara. The product in this research and development was Smart Apps Creator (SAC) mathematics media based on the local wisdom of the Mantingan Mosque Jepara. data were collected through interviews, questionnaires, and documentation. Then, the data were analyzed by a combination analysis, namely qualitative descriptive analysis and conversion of quantitative to qualitative data. The score of the students’ responses was 3969 with a percentage of 93.4%; the average score was 4.67 with a very good category. The media could be used if it got a good score (3.40 < X 4.21) from the students response. Thus, it was concluded that Smart Apps Creator (SAC) media based on the local wisdom of the Mantingan Mosque Jepara was feasible to improve students’ understanding of the concept of geometry at Grade VI Elementary Schools in Kecamatan Kembang, Kabupaten Jepara.